Foreign aid for Indian NGOs : problem or solution? - Sundar, Pushpa (New Delhi ; New York : Routledge, 2010)
Covers the period, 1950-2010.
Includes bibliographical references (p. [334]-349) and index.
Keywords: Economic assistance -- India; Non-governmental organizations -- India -- Finance; Nonprofit organizations -- India -- Finance